The life and death of ancient cities: a natural history - Woolf, Greg (Oxford University Press, 2020)
The story of ancient cities from the end of the Bronze Age to the beginning of the Middle Ages: a tale of war and politics, pestilence and famine, triumph and tragedy, by turns both fabulous and squalid.